Difficulties of digitalization: information technology in business, science, management education - T. Yu. Krotenko; M. I. Kanunikova; O. V. Lesnikova (Путеводитель предпринимателя)
Changes in Russia and the world are persistently pushing business, science and education to step into the digital space. At the same time, organizations, regardless of their field of activity, require a certain readiness, without which any digital innovation would be premature or unnecessary. However, it is not only the «digital maturity» of an organization that affects the success of its transformation towards the use of new digital technologies. The ability of workers and the organization as a whole to experiment is also important, as well as a certain enthusiasm, which is based on awareness of the progress in the field of information technology.